Seed Endophytic Achromobacter sp. F23KW as a Promising Growth Promoter and Biocontrol of Rhizoctonia Root Rot of Fenugreek - Ehsan M. Rashad; Dalia M. Shaheen; Abdulaziz A. Al-Askar; Khalid M. Ghoneem; Amr Abker Arishi; El Sayed A. Hassan; WesamEldin I. A. Saber (Molecules, 2022)
Root rot is one of the most significant soil and seed-borne fungal diseases, limiting the cultivation of fenugreek plants. Endophytic bacteria and their natural bioproducts have emerged as growth promoters and disease suppressors in the current era. Despite limited research, seeds are a good funder of endophytic microbiomes, which are transmitted from them to other seedling parts, thereby providing a shield against biotic and abiotic anxiety and promoting the growth at early germination and later stages. The current study evaluated the hypothesis that seed endophytic bacteria and their lytic enzymes, growth promotors, and antifungal molecules can induce growth, and inhibit root rot disease development at the same time. The isolation trial from fenugreek seeds revealed a lytic Achromobacter sp., which produces indole acetic acid, has antifungal compounds (e.g., 2-Butanol, 3,3’-oxybis-), and reduces the growth of Rhizoctonia solani by 43.75%. Under the greenhouse and natural field conditions, bacterial cells and/or supernatant improved the growth, physiology, and yield performance of fenugreek plants, and effectively suppressed the progress of root rot disease; this is the first extensive study that uses a new seed-borne endophytic bacterium as a plant-growth-promoting, and biocontrol tool against the sclerotia-forming; R. solani; the causative of fenugreek root rot.